Republic of Indonesia - Information, Knowledge, and Behavior : Evaluating Alternative Methods of Delivering School Information to Parents - Cerdan-Infantes, Pedro; Filmer, Deon (World Bank, Washington, DC, 2015)
Improving education outcomes by disseminating information to parents and thereby encouraging them to become more actively engaged in school oversight is attractive since it can be done relatively cheaply. This study evaluates the impact of alternative approaches to disseminating information about a school grants program in Indonesia on parent knowledge about the program in general, knowledge about the implementation of the program in their child’s school, and participation in school activities related to the program as well as beyond it. Not all dissemination approaches yielded impacts, and different modes of dissemination conveyed different types of information best, resulting in different impacts on behavior. Specifically, the low-intensity approaches that were tried - sending a letter from the principal home with the child, or sending a colorful pamphlet home with the child - had no impact on knowledge or participation. On the other hand, holding a facilitated meeting with a range of school stakeholders or sending targeted short message services (SMSs) to parents did increase knowledge and participation. Facilitated meetings mostly increased overall knowledge and fostered a feeling of transparency on the part of parents, which resulted in greater participation in formal channels for providing feedback to the school. SMSs increased knowledge about specific aspects of the program, such as the grant amount, and tended to increase participation through informal channels.